Impact of Entrepreneurial Orientation, Social Capital, and Technological Innovation on Competitiveness of MSMEs in Kintamani, Bali - Merung, Arteurt Yoseph; Dwi Susanti, Ida Ayu Made; Komang Juniasih, Ida Ayu (Sinergi International Journal of Management and Business, 2024)
This study looks at how social capital, technological innovation, and entrepreneurial orientation affect the competitiveness of MSMEs (micro, small, and medium enterprises) in Kintamani, Bali. The relationship between entrepreneurial behaviour, community interaction, technology adoption, and business competitiveness was investigated through quantitative analysis using a sample of 276 firms with random sampling technique and indicator comparison in SEM-PLS. Findings indicate a strong positive correlation between competitiveness, social capital, technological innovation, and entrepreneurial behaviour. In addition, this study reveals how social capital serves as a moderator to strengthen the beneficial effects of entrepreneurial mindset on competitiveness. The model shows a good fit, highlighting how well it captures the complex dynamics within Kintamani's distinct cultural and geographical environment. The findings of this study provide implications in enhancing MSME competitiveness, and practical insights that will direct plans for sustainable growth in this unique region by focusing on improving social capital, adapting to technology and increasing the level of entrepreneurial orientation for MSMEs in Kintamani Bali.